AN INTELLIGENT CYBER SECURITY DETECTION AND RESPONSE PLATFORM - Zhuo, Song; Hong, Yang Yu; Palaoag, Thelma D. (International Journal For Research In Advanced Computer Science And Engineering, 2022)
To further solve the cyber security challenges faced by the digital transformation of the Philippines university industry. This paper designed and proposed a cyber security detection and response platform (CSDRP), which can deal with traditional network security problems, improve the network security management capabilities of universities, and provide a method for real-time monitoring of network status and network security response in universities. With the outbreak of the epidemic, many universities in the Philippines have launched online courses and online services. These online courses and online services continue to proliferate, and with them come a host of cyber security risks and hidden dangers. CSDRP extracts logs through the traffic probes, and the platform performs correlation analysis on many security logs, combines relevant models and machine learning algorithms and generates response logs, which can be responded to and linked with policies, and finally presents relevant threats visually. This study deploys the platform in the actual network environment. The experimental results show that it provides accurate threat warnings, as well as good real-time detection and visualization of cyber threats, and can collect logs from different data sources in real time. linkage of safety equipment.